2010
DOI: 10.3109/0142159x.2010.490280
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of temporal bone anatomy learning with computer 3D rendered imaging softwares

Abstract: Aim: To determine whether the use of 3D anatomical models is helpful to students and enhances their anatomical knowledge. Methods: First year undergraduate students on the speech therapy or hearing aid practitioner courses attended either a lecture alone or a lecture followed by a 3D anatomy based tutorial, the latter which was also attended by ENT residents. Participants who received the tutorial were free to use the 3D model on the university computers or on their home computer and were then asked to answer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 17 publications
2
60
0
3
Order By: Relevance
“…Medical students often experience difficulties obtaining adequate spatial understanding of three‐dimensional (3D) anatomy from two‐dimensional (2D) images, such as those in anatomy books and on the internet (Battulga et al, ; Berney et al, ). This may be due to the fact that it is difficult for students in general to mentally rotate static, 2D illustrations (Beermann et al, ; Venail et al, ). Moreover, due to the complexity of anatomy, medical students and clinicians in training alike experience difficulties in recognizing anatomy in the clinical setting (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Medical students often experience difficulties obtaining adequate spatial understanding of three‐dimensional (3D) anatomy from two‐dimensional (2D) images, such as those in anatomy books and on the internet (Battulga et al, ; Berney et al, ). This may be due to the fact that it is difficult for students in general to mentally rotate static, 2D illustrations (Beermann et al, ; Venail et al, ). Moreover, due to the complexity of anatomy, medical students and clinicians in training alike experience difficulties in recognizing anatomy in the clinical setting (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, the use of these e‐learning tools within face‐to‐face anatomy courses has been detailed at numerous institutions (Sugand et al, ; Boyce, ; Gaitskell‐Phillips et al, ; Barbeau et al, ; Attardi and Rogers, ), and their popularity has inspired many researchers and educators to create their own anatomical e‐learning modules (Nicholson et al, ; Brenton et al, ; O'Bryne et al, ; Raynor and Iggulden, : Durham et al, ; Hassinger et al, ; Sergovich et al, ; Adams and Wilson, ; Doubleday et al, ; Preece et al, ; Allen et al, ). While previous publications that have examined the impact of e‐learning tools on student knowledge have demonstrated that e‐learning tools are more effective than traditional study methods (e.g., cadaveric dissection, textbook learning; Elizondo‐Omaña et al, ; Qayumi et al, ; Glittenberg and Binder, ; Nicholson et al, ; Hisley et al, ; Venail et al, ; Codd and Choudhury, ), most have demonstrated that e‐learning tools developed by individual researchers either do not offer an advantage or actually disadvantage students when compared with traditional instructional methods (Garg, ; Garg et al, ; 2002; Kurihara et al, ; Levinson et al, ; Keedy et al, ; Preece et al, ; Saltarelli et al, ; Webb and Choi, ; Mathiowetz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Slide sections, including in virtual microscopy, therefore require students to interpret a range of artefactual changes that occur through cross-sections of a tissue. Several studies report good student feedback on the use of interactive, virtual 3D anatomy models (Codd & Choudhury, 2011;Venail, Deveze, Lallemant, Guevara, & Monaind, 2010). Medical models that allow user control (Estevez, Lindgren, & Bergethon, 2010;Meijer & van den Broek, 2010;Nicholson, Chalk, Funnel, & Daniel, 2006;Tam et al, 2010) have been evaluated particularly positively.…”
Section: Introductionmentioning
confidence: 99%